Análise comparativa de uma planta de etanol de milho e de cana-de-açúcar - Marchetti, Leonardo Schirrmeister (Universidade Federal de São Carlos, 2023)
Brazil is one of the main ethanol producers in the world, with sugarcane as the main source of raw material for its production, while other countries like the United States have a significant share of the ethanol market using corn as raw material. In recent years, sugarcane production has not grown significantly and new corn-based ethanol plants have been implemented in Brazil, mainly in the Midwest region, thus reducing the participation of sugarcane in ethanol production, although it is still the main raw material used. In this sense, this work aims to develop a comparison between the two plants with a focus on Brazil, using the SWOT Analysis methodology (S - Strengths, W - Weaknesses, O - Opportunities, T - Threats), seeking to identify from the literature the points that hinder or facilitate the implementation of a project in Brazil using the different sources in the internal environment (plant operation) and the external environment (macro vision of the project), building a SWOT Matrix for each project. Through the present work it was possible to raise as main points that facilitate a corn ethanol plant the high agricultural production, the corn composition, the project maturity period, and the possibility of corn storage, while for sugarcane it was listed the energy production, the high productivity of sugarcane per hectare, possibility of E2G production, favorable environmental issue, co-products and possible lower exposure to the external market. Analyzing the points that hinder the implementation of the corn project, one can mention the energy consumption in the industrial process, the unfavorable environmental issue, and greater exposure to the foreign market.
Comparative analysis of a corn and sugar cane ethanol plant
Keywords: Usina; Etanol; Cana-de-açúcar; Milho; Análise SWOT; Ethanol plant; Sugarcane; Corn; SWOT analysis; ENGENHARIAS::ENGENHARIA QUIMICA